COPPER OXYCHLORIDE APPLIED ALONE TO CONTROL CITRUS BLACK SPOT - Fonseca, Antonio Eduardo [UNESP]; De Goes, Antonio [UNESP]; Pereira, Fernanda Dias [UNESP] (Univ Fed Rural Semi-arido-ufersa, 2019)
Citrus black spot (CBS) is a disease caused by the Phyllosticta citricarpa fungus that causes lesions in fruits and, in more severe stages, fruit drops. The use of systemic fungicides is the main control measure for CBS; however, an alternative control measure is the use of cupric fungicides applied alone with short intervals. Therefore, the objective of the present work was to evaluate the effect of applications of copper oxychloride at different rates on the control of CBS. The experiment was conducted in Bebedouro, SP, Brazil, in the 2014/2015 crop season, in a randomized block design, using a Citrus sinensis variety (Valencia). The treatments consisted of copper rates (zero - control; 31, 24.5, 18.5, 12.2, and 9.1 mg of metal copper per cubic meter of canopy) using copper oxychloride (concentrated suspension - CS; 588 g L-1 of copper oxychloride or 350 g L-1 of metal copper), and an additional treatment with application of a cupric fungicide (cuprous oxide) and a strobilurin fungicide. The applications were carried out with 14-day intervals, starting when 2/3 of the petals of the plant's flowers were fallen, totaling 14 applications. The incidence and severity of CBS were evaluated five times with 30-day intervals up to mid-November, when the fruits were harvested. The data were used to calculate the area under the disease progress curve (AUDPC). Applications of copper oxychloride CS at rates of 31 and 24.5 mg m(-3) with 14-day intervals are efficient for the control of CBS, with similar efficiency to the farm standard treatment.
Keywords: Citrus sinensis; Chemical control; Fungicide; Phyllosticta citricarpa